Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 1 - 1.6 - Other Types of Equations - 1.6 Exercises - Page 128: 50


0, 1, 3/5

Work Step by Step

$4x^2(x-1)^\frac{1}{3}+6x(x-1)^\frac{4}{3}=(x-1)^\frac{1}{3}(4x^2+6x(x-1))=0$Hence either $(x-1)^\frac{1}{3}=0$, giving x=1 or $(4x^2+6x(x-1))=10x^2-6x=2x(5x-3)=0$ giving x=0 or 3/5
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.